Fluvial Sandstone Reservoir Connectivity - Herman Darman (Berita Sedimentologi, 1997)
This essay discusses the conduits and partitions of the fluvial rocks which are controlled by the depositional origin. Some reservoirs of producing hydrocarbon fields are reviewed to show some cases of the hydrocarbon recovery processes.